Assessment of Plant Community Characteristics in Natural and Human-Altered Coastal Marsh Ecosystems - Meixler, Marcia S.; Kennish, Michael J.; Crowley, Katherine F. (Estuaries and coasts, 2018)
Salt marsh ecosystems provide many critical ecological functions, yet they are subject to considerable disturbance ranging from direct human alteration to increased inundation due to climate change. We assessed emergent salt marsh plant characteristics in the Tuckerton Peninsula, a large expanse (~ 2000 ha) of highly inundated habitat along the southern New Jersey coast, USA. Key salt marsh plant parameters were monitored in the heavily grid-ditched northern segment, Open Marsh Water Management (OMWM) altered central segment, and the shoreline altered southern segment of the peninsula in the summer months of 2011 and 2013. Plant species composition and three metrics of abundance and structure (maximum canopy height, percent areal cover, and shoot density) were examined among marsh segments, along transects within segments, seasonally by month and between years. Despite seasonal or annual variability, the northern segment of the marsh differed in plant species composition from the central and southern segments. This difference was partly due to greater percent areal cover in the northern segment of upper marsh species such as Spartina patens and Distichlis spicata. S. patens also exhibited higher shoot densities in the northern segment than the central segment. Despite the higher abundance of upper marsh species, marsh surface elevations were lower in the northern segment than in the central or southern segments, suggesting the influence of altered hydrology due to human activities. Understanding current variation in the emergent salt marsh vegetation along the peninsula will help inform future habitat change in other coastal wetlands of New Jersey and the mid-Atlantic region subject to natural and anthropogenic drivers.